The struggle between equity and efficiency: do Nordic countries have a free lunch? - Norbert Berthold; Alexander Brunner (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2008)
Although there is a vast theoretical literature on the existence of a tradeoff between equity and efficiency, empirical investigations often fail to find evidence for this proposition. Furthermore there are hints that some social models in Europe can cope better with this trade-off and are actually able to provide what economists call a free lunch. In this paper we use data from the Luxembourg Income Studies (LIS) to evaluate (a) whether there really exists something like a free lunch and (b) whether some social systems are actually better in coping with the trade-off between equity and efficiency.
Keywords: D61; D63; 330; equity; efficiency; tradeoff; welfare states